KOMUNITAS RHIZOBAKTERIA TANAMAN TEH DENGAN APLIKASI FORMULA BIOIMUNIZER (Chryseobacterium Sp DAN Bacillus Sp) BERDASARKAN GEN 16S rRNA - Agnistisya Widaranti; Siti Nur Jannah; Hermin Pancasakti Kusumaningrum; Dwi Ningsih Susilowati (Jurnal Akademika Biologi, 2016)
Commodity of tea (Camellia sinensis) has an important role in the national economy, especially in the field of agro-industries. Based on data obtained from the Directorate General of Plantation, the tea plant productivity declined over the last few years. This is due to the pest attack which result in decreasing the productivity of the tea plant. Increased crop productivity of tea have been done, such as the use of herbicides and insecticides, but until now there is very little effort to increase the production of tea plants by the use of biological agents. Chryseobacterium sp and Bacillus sp are rhizobacteria in tea rhizosphere that could potentially be used as a biocontrol agent (bioimmunizer). The purpose of this study is to determine the community rhizobacteria in tea soil with the addition of bioimmunizer based on 16S rRNA gene using T-RFLP technique. The method used in this research is T-RFLP technique (Terminal Restriction Fragment Length Polymorphism) using enzymes Msp I and Rsa I. The calculated value are relative abundance, Shannon diversity index (H '), evenness index (E), and dominance index. The results of this study indicate that soil samples with the addition of bioimunizer consisting of Arthrobacter sp, Bacillus sp, Actinobacteria, and Chryseobacterium sp.Keyword: T-RFLP, Chryseobacterium sp, Bacillus sp